2005
DOI: 10.1002/ajmg.a.30805
|View full text |Cite
|
Sign up to set email alerts
|

Spondylo-mega-epiphyseal dysplasia with prominent upper limb mesomelia, punctate calcifications, and deafness

Abstract: We report on a previously undescribed form of skeletal dysplasia with rhizomelic, acromelic, and prominent mesomelic shortening, distal ulnar epiphyseal and pubic punctate calcifications (stippling), mega-epiphyses, platyspondyly, anterior beaking of the vertebrae, and sensorineural hearing loss. We compare this case to the other reported forms of skeletal dysplasias, particularly the mesomelic, acromesomelic, and mega-epiphyseal disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Further, the patients described by Giedion et al [1982] had normal stature rather than short stature. Nevertheless, a severe patient that shares many features of OSMED, but with markedly defective ossification of vertebral body centers and enlarged epiphyses was reported by Agarwal et al [2003], and yet another patient was reported with stippling of the epiphyses [Agarwal et al, 2005]. This phenotypic variability may reflect the fact that haploinsufficiency and mutations with a dominant negative effect on collagens generally result in different phenotypes or degrees of severity [Melkoniemi et al, 2000].…”
Section: Discussionmentioning
confidence: 92%
“…Further, the patients described by Giedion et al [1982] had normal stature rather than short stature. Nevertheless, a severe patient that shares many features of OSMED, but with markedly defective ossification of vertebral body centers and enlarged epiphyses was reported by Agarwal et al [2003], and yet another patient was reported with stippling of the epiphyses [Agarwal et al, 2005]. This phenotypic variability may reflect the fact that haploinsufficiency and mutations with a dominant negative effect on collagens generally result in different phenotypes or degrees of severity [Melkoniemi et al, 2000].…”
Section: Discussionmentioning
confidence: 92%
“…Further, the patients described by Giedion et al 1982 had normal stature rather than short stature. Nevertheless, a severe patient that shares many features of OSMED, but with markedly defective ossification of vertebral body centers and enlarged epiphyses was reported by Agarwal et al 2003, and yet another patient was reported with stippling of the epiphyses [Agarwal et al, 2005]. This phenotypic variability may reflect the fact that haploinsufficiency and mutations with a dominant negative effect on collagens generally result in different phenotypes or degrees of severity [Melkoniemi et al, 2000].…”
Section: Discussionmentioning
confidence: 99%